The use of fall risk-increasing drugs among older people in nursing homes - Lee, Shiow Ling; Marhanis Salihah Omar,; Adliah Mhd Ali,; Mohd Makmor-Bakry, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Medication use is one of the modifiable risk factors that causes falls. Falls are the leading cause of injury among elderly people. The incidence of falls does significantly impact elderly people‘s independence in carrying out their regular activities. This study aimed to determine the prevalence of drugs that cause falls and the fall risk status among elderly people residing in nursing homes. A cross-sectional study was conducted on residents in 27 long term care facilities in Malaysia from March 2018 until November 2018 using a researcher-assisted questionnaire. A total of 212 residents were recruited in this study. A majority of the residents were taking at least one fall-risk increasing drug (FRIDs) or orthostatic drug (ODs) (n=145, 68.4%), with two-thirds of them presenting high risk of falling (n=95, 65.5%). A significant association was found between the use of beta-blocking agents (p=0.033), renin-angiotensin system inhibitors (p=0.038), length of stay in facilities (p=0.031), frailty status (p<0.001), number of drugs in total (p=0.010) and as needed (p=0.025) with an increased risk of falls. Therefore, a majority of the elderly people residing in nursing homes were proven to be prone to the use of fall-risk medications. Frail elderly people have a higher risk of falling compared to those who were non-frail.